Konsep Hijab Dalam Pemikiran Fatima Mernissi - Ida Novianti (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2011)
As a feminist, Fatima Mernissi aware og the need for the participant of Muslim women to participate in improving the situation being experienced by women. This time there was a shift role and position of Muslim women than in past centuries, especially when the Prophet was still alive. First, the friends of women who have position of honor and can participate in various activities. In fact, the Prophet also accept the idea and the idea came from women. After the Prophet's death and the years thereafter, the condition began to change. The caliph concerned the role of women in the public and tried to stop the women's steps. One of the most affective way is to adopt a female hhijab and away from public life or locked the in a Harem. This was done to protect women from a variety of change, protection of the moral decay of Western culture with hijab and close them from the outside world is an echo of the heart are closed. Hijab resurgence in the era of the 2000s to Mernissi is a symbol of men's fear of the roles in modern times.